Implementation of the TGT (Team Game Tournament) Method to Improve Students Vocabulary Mastery: Penelitian - Siti Kurnia Hasbi; Zuhri Efendi (Jurnal Pustaka Cendekia Pendidikan, 2026)
Vocabulary mastery is essential for developing students' English language skills; however, many elementary school students still experience difficulties in learning and retaining English vocabulary because of conventional teacher-centered instruction. This study aimed to investigate whether the implementation of the Teams Games Tournament (TGT) method significantly improves the vocabulary mastery of Grade 5 students at Madrasah Ibtidaiyah Muhammadiyah Blangpidie. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 30 Grade 5A students. Data were collected through a 20-item multiple-choice vocabulary test administered before and after the treatment and analyzed using IBM SPSS Statistics Version 27. The results showed that the students' mean score increased from 43.33 on the pre-test to 82.67 on the post-test. The paired-samples t-test revealed a statistically significant difference between the two tests (p < 0.001), indicating that the TGT method significantly improved students' vocabulary mastery. These findings suggest that TGT is an effective cooperative learning strategy for enhancing vocabulary learning through active participation, teamwork, and enjoyable classroom activities.